Zero (short) time-lapse seismic repeatability test at naylor field, Australia - Al Jabri, Y.; Urosevic, Milovan (European Association of Geoscientists and Engineers, EAGE, 2012)
High seismic repeatability is critical to the monitoring program of the Naylor Field because of the small time-lapse effect related to C02 injection into depleted gas reservoir (Naylor). To be able to obtain reliable seismic from a time-lapse seismic survey, the repeatability of the time-lapse survey must be determined. This can be achieved by performing zero-time repeatability tests through the acquisition and reacquisition of data in the same area before any changes occur in the reservoir. By comparing the analysis of multiple repeated pre-stack 2D surface seismic and VSP delta, differences maybe established to minimize near-surface system effects.